Austérité et gestion dans les universités québécoises: une analyse des perceptions de directeurs de département - Crespo, Manuel; Hache, Jean B.; Gendron, Carmen; Vanier, Yves (Canadian Journal of Higher Education, 1986)
This article discusses different aspects of the management of budgetary austerity in higher education. Its database consists of in-depth interviews with twenty-five department chairpersons from six Québec universities. In general, strategic choices imposed by university administration are reactive and aimed at meeting short-term government objectives. Among the strategies more dependent on departmental choice, some are proactive. Nevertheless, the range of choices is limited by overall constraints. Longer term solutions to cope with the crisis in higher education proposed by chairpersons are problematic since they stem from somewhat contradictory views on the major role of the university as an institution.